Dynamics of Collapse of Optical Pulses in Kerr Medium Placed in a Harmonic Potential - Van, Cao Long; Khoa, Dinh Xuan; Hung, Nguyen Viet; Trippenbach, M. (Communications in Physics, 2012)
We consider the propagation of optical pulses in Kerr medium placed in a harmonic potential for 2D case in framework of Variational Approximation (VA). We will use two types of trial function: gaussian and hyperbolic secant. We will show that for the values of the nonlinearity parameter bigger than a certain critical value the pulses will collapse. This corresponds to the physical situation when the self-focusing dominates over the dispersion and diffraction. We will confirm this by numerical calculations which are in excellent agreement with the VA predictions.